Factors influencing long-term survival after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for pseudomyxoma peritonei originating from appendiceal neoplasms. Issue 3 (19th February 2019) - van Eden, W J; Kok, N F M; Snaebjornsson, P; Jóźwiak, K; Woensdregt, K; Bottenberg, P D; Boot, H; Aalbers, A G J
Abstract: Background: Pseudomyxoma peritonei (PMP) is a rare disease, most commonly of appendiceal origin. Treatment consists of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS–HIPEC). The aim of this study was to identify prognostic factors for recurrence and survival. Methods: This was an observational study using a prospectively designed database containing consecutive patients with PMP originating from the appendix, undergoing CRS–HIPEC at a tertiary referral centre between 1996 and 2015. Histopathological slides were reassessed. Cox regression was used for multivariable analyses. Results: Of 225 patients identified, 36 (16·0 per cent) were diagnosed with acellular mucin, 149 (66·2 per cent) had disseminated peritoneal adenomucinosis (DPAM) and 40 (17·8 per cent) had peritoneal mucinous carcinomatosis (PMCA). The 5-year overall survival (OS) rates were 93, 69·8 and 55 per cent respectively. Recurrence was observed in 120 patients (53·3 per cent), 39 of whom (17·3 per cent) were treated with a second CRS–HIPEC procedure. Factors independently associated with poor disease-free survival were six or seven affected regions (hazard ratio (HR) 6·01, 95 per cent c.i. 2·04 to 17·73), incomplete cytoreduction (R2a resection: HR 1·67, 1·05 to 2·65; R2b resection: HR 2·00, 1·07 to 3·73), and more than threefold raised carcinoembryonic antigen (CEA) and/or carbohydrate antigen (CA) 19-9 level (HR 2·31, 1·30 to 4·11). Factors independently associated with poorer OS were male sex (HR 1·74, 1·09 to 2·77), incomplete cytoreduction (R2a resection: HR 1·87, 1·14 to 3·08; R2b resection: HR 2·28, 1·19 to 4·34), and more than threefold raised CEA and/or CA19-9 level (HR 2·89, 1·36 to 6·16). Conclusion: CEA and CA19-9 levels raised more than threefold above the upper limit identify patients with PMP of appendiceal origin and poorer survival. Graphical Abstract: Pseudomyxoma peritonei does not recur in almost half of patients who are treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Prognosis depends on sex, completeness of cytoreduction and level of serum tumour markers. Survival related to levels of tumour markers